Analysis of flow and heat transfer inside different filter designs - Lekoko, Modisawatsona Lucas (North-West University (South Africa), 2023)
This research project’s main purpose is to theoretically investigate internal flow, heat and mass transfer inside different filter designs. The efficiency of filtering methods used to reduce/remove particles deposited in a liquid varies greatly depending on the type of par- ticles, the quality of filter media and filter design. As a result, it is ideal for engineers and scientists to design filters based on mathematical models (scientific evidence) that predict the dynamics of the filters to provide a better understanding of the flow, heat and mass transfer during the filtration process when designing filters. It is vital to have a design that yields optimal balance between the parameters that restrict the particles and allows de- sirable outflow and heat transfer. Pursuing to understand momentum variation, heat and mass transfer during the filtration process. The mathematical models presenting different filter designs under investigation will be formulated using continuity, momentum, concen- tration and energy conservation laws, along with physical laws representing forces that affect the process according to each filter design. The flow and heat transfer models un- der investigation are solved analytical and semi-analytical or numerical in cases where the model(s) could not be solved analytically. The obtained solutions of each model are then used to analyse flow, heat and mass transfer to understand the dynamics of each model and to highlight an optimal design amongst models considered in this research project. The study also aims to study the effects of various parameters in detail according to each filter design to have evidence-based findings that lead to optimal permeate production.
PhD (Applied Mathematics), North-West University, Potchefstroom Campus
Keywords: Different filter designs; Flow and heat transfer; Analytical and numerical analysis; Steady/Unsteady filtration process; Magnetohydrodynamic fluid; Optimal permeates